Adjustment problems of the students in Medina National Comprehensive High School as related to certain variables and their implications to guidance - Tarongoy, Myrna C. 1953- (1978)
This study identified the adjustment problems of the students in Medina National Comprehensive High School in the school-year 1978-1979. It used the normative survey method. The number of adjustment problems of the students were correlated with the different variables mostly on mental fitness and family background. It also highlighted the need for a more stable guidance program in schools to meet the needs and problems of the students.
Appendices: leaves 117-126
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Medina National Comprehensive High School -- Students; Adjustment (Psychology).; Adolescent psychology -- Philippines